An Argument on Rhetorical Style - Lund, Marie, 1968- (Book collections on Project MUSE., 2017)
An Argument on Rhetorical Style' seeks to sharpen a tool that is too often blunted by multiple, overlapping, and vague definitions. Lund examines the historical, modern, and postmodern concepts of style, allowing the synthesis of three principle epistemological outlooks, the topics of 'style as man', 'style as dress', and 'constitutive style', which in turn illuminate the analysis of different rhetorical styles. Lund argues for a re-theorization of style in the framework of constitutive rhetoric. Theory is balanced by a sharp focus on the strategic aspects of style, with reference to numerous real-world examples from contexts as varied as political speeches, hip-hop lyrics, and newspaper opinion columns. Two chapters explore 'feminine style' and 'provocative style' through detailed rhetorical analysis. Finally, Lund combines theory and practice as applied to speechwriting, showing her new approach to rhetorical style. This book will be valuable to students and scholars of language looking for a fresh interpretation of style and rhetoric, as well as opening up new areas of use for these classic concepts.